FEATURES OF FUNCTIONALITY OF CARDIOVASCULAR SYSTEM OF UNIVERSITY STUDENTS, LIVING IN THE INDUSTRIAL CITIES OF EASTERN SIBERIA - O. Yu. Katulskaya (Acta Biomedica Scientifica)
The aim of this work was to evaluate the adaptive capacity of a technical college student living in an industrial city in Eastern Siberia. The paper presents the results of the assessment offunctionality of the cardiovascular system of students of technical and economic disciplines. In the present study we used physiological research methods, including the assessment of the functional state of the cardiovascular system, taking into account the reactions to physical exercise and evaluation of adaptive capacity with the calculation of the index of functional changes (1F1) by R.M. Baevsky. To assess the level of stress in the regulation of the cardiovascular system determines the type of self-regulation of blood circulation. Average levels of systolic blood pressure inyoung economists somewhat lower (128,3 ± 2,0 mm Hg) than in boys of technical specialties, which is more favorable prognostic sign. Do students and economists across the figure was significantly higher (119,5 ± 1,7 mm Hg; p < 0,05) than that of female students of technical specialties. 1n 27,3 ± 9,3 % of boys and 45,4 ± 15,0 % of girls of technical specialty we observed normotonic response to physical activity (p < 0,05). Among students of economics from the fixed normotonic type of reaction from 40,0 ± 21,9 % of boys and 50,0 ± 8,5 % of girls. Hypertensive type of response was found in 68,2 ± 9,4 % of boys and 45,4 ± 15,0 % of girls technical specialty (p < 0,05). 1n addition in 4,5 ± 4,3 % of surveyed youths and 9,1 ± 8,4 % of girls of the same type of specialty marked dystonic reactions to physical activity, which, as a hypertensive, is unfavorable. Among students of economics from hypertensive type of response was found in 60,0 ± 21,9 % of boys and 42,3 ± 8,4 % of girls. Dystonic reaction to physical activity only found in girls (7,7 ± 5,1 %). 1t was revealed that 63,9 % of students had reduced functionality of the functional voltage detected in 79,0 % of boys and 48,8 % girls among all the surveyed students. 1n male students of technical specialties functional stress occurred 2,4 times more often than in female students, in those of economic specialization -1,5 times more often than in girls. The girls who are enrolled in the economic stream functional stress occurred 1,6 times more often in comparison with girls of technological flow. The results show a decrease in adaptive capacity in a cohort of students.